An Investigation about Stability in Waves of Large Pleasure Yachts - Nicola Petacco; Valerio Ruggiero; Paola Gualeni (Journal of Marine Science and Engineering, 2023)
The IMO’s second-generation intact stability criteria (SGISc) have been applied to a set of seven megayacht units ranging from 40 m to 80 m. The application aims to evaluate their stability performance in a seaway. The assessment is based on two vulnerability levels, and the related criteria rely on the physics of the phenomena under investigation (dead ship condition, excessive acceleration, parametric rolling, pure loss of stability, and surf-riding). At the same time, SGISc provide methodological approaches to consider possible operational limitations related to the geographical area the vessel is meant to sail. Results of the comprehensive analysis carried out for the selected megayacht units are presented in term of limiting KG curves. Outcomes pointed out that inconsistencies among vulnerability levels still exist. Further comments about the relation of the investigated vessel typology and relevant operational profile have been reported. In addition, systematic analysis of the effect of the main design parameter on ship rules compliance has been carried out.